Analysing Notions , Perceptions and Truth of Transgenders with the help of Lili : The Portrait of the First Sex Change. (International Journal of Food and Nutritional Sciences, 2022)
The word transgender is often used as an umbrella term for persons whose identity, gender expression or behaviour does not conform to the biological sex to which they were assigned at birth. Transgender people were always a mystery to society. Some consider them as an abomination of natural order where as some consider them with pity. This paper focuses on the general notion, perception and truth about transgender by analysing literary works and adaptations